The Role and Thought of The Nahdlatul Ulama-Muhammadiyah On Humanity - Suprapto Suprapto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2021)
Concern for humanitarian and health issues, several parties including NU and Muhammadiyah were involved in handling the pandemic. Organizing the community in several aspects, such as appeals in mosques, appeals to educational institutions and Islamic boarding schools, appeals for health protocols, and appeals for vaccinations. Muhammadiyah instructs that educational activities at all levels are aligned with government policies which are coordinated through the relevant assemblies. Through NU Care-Laziznu, they carried out a movement to help the poor or residents affected by the COVID-19 pandemic. NU formed a covid task force to mobilize NU residents to help residents affected by COVID-19. NU as a student movement organization, is actively involved in the struggle of the Indonesian nation. Islam Nusantara and Islam Berkejuan are the first, emphasizing locality with Islam, while the second focuses on globalization. Through the movement in Islamic boarding schools, NU as a space for religious studies (educational function), dialogue with local culture (socio-cultural function) and training on problems in society (socio-political function). Tajdid initiated by Muhammadiyah is to put a solid religious view in the building of faith based on the Al-Quran and As-Sunnah and develop it for a progressive and civilized life. In its acceptance of ijtihad, the tarjih assembly is based on three main points, namely: 1) ijtihad bayani (explaining the mujmal texts of the Qur'an and Hadith); 2) ijtihad qiyasi (stipulating legal provisions that do not exist in the Al-Quran and Hadith; 3) ijtihad istishlahi (stipulating laws that do not have texts specifically based on illat).